The Impact of Job Burnout on Employees’ Safety Behavior Against the COVID-19 Pandemic: The Mediating Role of Psychological Contract - Liu, Hui; Du, Yuexin; Zhou, Huiwen (Frontiers in Psychology, 2022)
Employee safety behavior is critical for occupational health in work environments threatened by the COVID-19 pandemic. Meanwhile, the widespread and increasingly serious job burnout of employees is a complex and difficult problem for enterprises to handle during any epidemic. Therefore, it is helpful to identify and discuss job burnout and other main psychological factors that affect safety behavior to find appropriate solutions. Using the PLS-SEM method, the study explored the relationship between job burnout and safety behavior against the epidemic, as well as the mediating role of psychological contract. According to the local guidelines for controlling COVID-19, this study revised the safety behavior scale. Data were collected by structured questionnaires in May to July 2020 from Chinese employees (N = 353) who resumed their work after the outbreak of the pandemic. The findings confirmed that job burnout has a negative impact on safety behavior, and psychological contract play a partial mediating role in mitigating the negative impact. Specifically, the transaction dimension and relationship dimension of psychological contract negatively affected safety behavior while the development dimension of the psychological contract was not directly related to safety behavior. It is suggested that enterprises should take effective measures to reduce employees’ job burnout and implement flexible psychological contract management and intervention, so as to effectively improve the performance of work safety behavior. Based on the multidimensional model, the findings of this study shed light on promoting safety behavior to prevent the spread of epidemics.